2015
DOI: 10.2147/copd.s84618
|View full text |Cite
|
Sign up to set email alerts
|

VitalQPlus: a potential screening tool for early diagnosis of COPD

Abstract: BackgroundThis study utilized a validated combination of a COPD Population Screener (COPD-PS) questionnaire and a handheld spirometric device as a screening tool for patients at high risk of COPD, such as smokers. The study aimed to investigate and pilot the feasibility and application of this combined assessment, which we termed the “VitalQPlus”, as a screening tool for the early detection of COPD, especially in primary care settings.MethodsThis was a cross-sectional study screening potentially undiagnosed CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Studies have demonstrated that a dual-combination assessment tool, namely VitalQPlus, which incorporates the COPD-PS questionnaire and the COPD-6 screener with an FEV1/FEV6 ratio of <75%, could be used by physicians to identify individuals at risk of COPD and to select patients for conventional spirometry. 29 This observation is similar to that in a meta-analysis; the authors of that meta-analysis suggested using a questionnaire as a prescreening test for microspirometry to improve COPD screening accuracy. 12 However, the prescreen use of a COPD-PS questionnaire followed by microspirometry with FEV1/FVC ratio calculations has not been validated and requires further investigation.…”
Section: Discussionsupporting
confidence: 73%
“…Studies have demonstrated that a dual-combination assessment tool, namely VitalQPlus, which incorporates the COPD-PS questionnaire and the COPD-6 screener with an FEV1/FEV6 ratio of <75%, could be used by physicians to identify individuals at risk of COPD and to select patients for conventional spirometry. 29 This observation is similar to that in a meta-analysis; the authors of that meta-analysis suggested using a questionnaire as a prescreening test for microspirometry to improve COPD screening accuracy. 12 However, the prescreen use of a COPD-PS questionnaire followed by microspirometry with FEV1/FVC ratio calculations has not been validated and requires further investigation.…”
Section: Discussionsupporting
confidence: 73%
“…For example, Soriano et al reported that the combination of COPD-PS and peak expiratory flow (PEF) measurements at recommended thresholds in primary care is a useful, reliable strategy for finding new COPD cases, leading to a 90% reduction in the number of spirometry tests performed [ 24 ]. COPD-PS combined with COPD-6 could potentially be used by clinicians to identify individuals at risk of COPD and to select patients for spirometry measurement [ 26 ]. Thus, we suggest that COPD-PS should be used with other tools, which may substantially reduce the number of unnecessary spirometry tests.…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus in literature about the great importance of early COPD diagnosis, enabling the establishment of measures that may alter the course of the disease, including pharmacological and non-pharmacological interventions and smoking cessation. 7 11 Assessment of respiratory obstruction in the early stages is critically dependent on the sensitivity of pulmonary function tests. 12 It has previously been observed that spirometric indices are not sensitive to small changes due to smoking.…”
Section: Introductionmentioning
confidence: 99%